Os Impactos do uso da Caderneta de Saúde da pessoa idosa e matriciamento nos indicadores de satisfação da equipe e dos idosos na Atenção Primária em Saúde - Bianco, Otávio Augusto Fernandes Marques (2023)
Aging brings new demands to health systems. Therefore, it is necessary to improve the management of health resources, as well as to promote preventive and patient-centered care. One of the ways is to carry out matrix support for continuing education about health management tools and that produce indicators, such as the Health Handbook for the Elderly (CSPI). Objectives: To evaluate the impacts of using the Health Handbook for the Elderly and the presence of a matrix support carried out by an aging manager on the health management indicators of the unit and satisfaction of the team and the elderly. Methodology: This is a study experimental, longitudinal with a quantitative and qualitative approach. For this purpose, 4 USF from a municipality in Minas Gerais were selected, separating them into 2 groups, Intervention (GI) and Control (GC), followed for 6 months. In addition, 157 elderly people were selected to carry out a satisfaction assessment. Both groups received qualifications regarding the importance of the multidimensional assessment (AMD) of the elderly, the use of CSPI, monitoring of outcomes and support materials for the intervention. In the intervention group, management and follow-up of elderly cases were carried out through the CSPI, with fortnightly matrix support. The variables number of completed CSPI and satisfaction were collected from the team, and from the elderly, their satisfaction through the Short Assessment Patient Satisfaction (SAPS) instrument before and after the intervention period. Data were tabulated and analyzed using the SPSS software, adopting a significance value of 0.05. The Mann-Whitney test was used for intergroup comparison, the Wilcoxon test for intragroup comparison and the chi-square test for categorical variables. The qualitative analysis was presented by the summary of the domains raised in the professionals' responses Results: For the intergroup analysis of the team, Initially, no professional from the evaluated teams used the CSPI, after the intervention there was a difference in filling out the CSPI between GC and IG, with 75 % of GI professionals started to use the CSPI, while the CG did not use the instrument. Regarding the satisfaction of elderly patients, an initial difference was found in the domains evaluated by the SAPS in the questions satisfaction with the effect of treatment/care (SAPS 1), GC (4.57 +/- 0.69) GI (4.09 +/ - 1.1); second question related to satisfaction with the professionals' explanations (SAPS 2) GC: (4.58 +/- 0.86) IG: (4.31 +/- 0.89); satisfaction with their own choices (SAPS 4) GC: (4.57 +/- 0.94) GI (4.26 +/- 0.76); satisfaction with consultation time (SAPS 6) GC: (4.81 +/- 0.72) IG: (3.90 +/- 1.33). After the intervention, these differences remained, with the exception of SAPS 6. There was also a difference in the question satisfaction with care (SAPS 7) GC: (4.75 +/- 0.53) IG: 4.39 (+/- 0 ,75) after the intervention. In the intragroup comparison of elderly patients, there was a difference in question SAPS 6, with an increase in the score in the initial GI (3.90 +/- 1.33) in the final (4.42 +/- 1.10) and a reduction in the score in the initial CG (4.81 +/- 0.72) final (4.26 +/- 1.32). In the intragroup comparison of the teams, there was difference only in the question related to the team's knowledge about the health of the elderly, mean initial GC: (3.17 +/- 0.86) final (3.76 +/- 0.86). Regarding the qualitative analysis, there was a change in the speech pattern between the CG and GI, in which the GI began to perceive an improvement in the service and referral flow, while the CG did not have this change. Discussion: Matrix support had no impact on the satisfaction scores of either the team or the elderly, evidencing the need for a longer intervention time and the influence of multiple factors on the satisfaction of both the team and the elderly. On the other hand, matrix support increased the number of CSPI completed by the team and the perception of their use and knowledge about the health of the elderly. This shows how teams need constant support and encouragement from management and specialist professionals. Conclusion: matrix support did not impact the levels of satisfaction of the team and the elderly, but it did impact the completion of the CSPI and the feelings related to the health of the elderly, showing its importance in strengthening the use of AMD in PHC and helping the team in formulating the longitudinal care plan for the elderly.